2018
DOI: 10.1063/1.5016049
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Investigation of ion aggregation in ionic liquids and their solutions with lithium salt under high pressure

Abstract: X-ray scattering measurements were utilized to probe the effects of pressure on a series of ionic liquids, N-alkyl-N-methyl-pyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr-TFSI) (A = 3, 6, and 9), along with mixtures of ionic liquid and 30 mol. % lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt. No evidence was found for crystallization of the pure ionic liquids or salt mixtures even at pressures up to 9.2 GPa. No phase separation or demixing was observed for the ionic liquid and salt mixtures. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 35 publications
14
36
1
Order By: Relevance
“…2,7,53,54 This peak is slightly shifted towards larger Q upon Li + salt addition (1.52 Å -1 for f = 0 and 1.57 Å -1 for f = 0.5) without modification of its shape and intensity. This contrasts with what is observed in other systems such as LiTFSI/Pyrrolidinium TFSI systems where a shift towards smaller Q was measured upon Li ion addition (this effect being related to the size of Li(TFSI) 2-anion 55 ). As already mentioned, the smaller peak at smaller Q is very sensitive to the amount of Li salt being added to the electrolyte.…”
Section: Structure Factor S(q)contrasting
confidence: 99%
“…2,7,53,54 This peak is slightly shifted towards larger Q upon Li + salt addition (1.52 Å -1 for f = 0 and 1.57 Å -1 for f = 0.5) without modification of its shape and intensity. This contrasts with what is observed in other systems such as LiTFSI/Pyrrolidinium TFSI systems where a shift towards smaller Q was measured upon Li ion addition (this effect being related to the size of Li(TFSI) 2-anion 55 ). As already mentioned, the smaller peak at smaller Q is very sensitive to the amount of Li salt being added to the electrolyte.…”
Section: Structure Factor S(q)contrasting
confidence: 99%
“…More recently a series of Molecular Dynamics studies by Canongia Lopes and coworkers appeared [29][30][31][32], proposing, on the basis of computational work, a scenario where alkyl domains and fluorous ones tend to segregate from the charged three-dimensional network. Although not focusing on fluorinated anions that lead to the formation of fluorous domains, several studies have been dedicated to the exploration of structural properties in pyrrolidinium-based ILs, merging diffraction and computational techniques [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The interest toward this feature is witnessed by the wealth of studies addressing its nature and dependence upon chemical nature of the ions, [25][26][27][28][29][30] temperature, 13,15,31 mixture composition, [32][33][34][35][36][37][38][39][40][41] and, only recently, pressure. [42][43][44][45] High pressure studies are an important tool to explore the details of microscopic and mesoscopic correlations in complex materials. Pressure changes allow investigating intermolecular interactions, by inducing density changes without introducing the chaotic perturbation that temperature changes induce.…”
mentioning
confidence: 99%
“…Pressure changes allow investigating intermolecular interactions, by inducing density changes without introducing the chaotic perturbation that temperature changes induce. As a matter of fact, while temperature dependence studies of morphology in RTILs have been reported in the past, 13,15,31 the pressure dependence of the mesoscopic organization in aprotic RTILs has been explored by means of experimental X-ray studies [42][43][44] and simulations [45][46][47][48][49][50] 42 Therein the progressive position shift and amplitude vanishing of the low Q peak centred at ca. 3 nm −1 had been observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation